Intermolecular interactions on amine-cured epoxy matrices with different crosslink densities. influence on the hole and specific volumes and the mechanical behavior - Blanco, M. (2009)
The architecture of an epoxy matrix was modified by curing the resin with mono-/diamine mixtures having identical chemical structures. Both hole volume and specific volume variations were studied by positron annihilation lifetime spec-troscopy and pressure-volume-temperature/density measurements, respectively. The average hole volume of the networks at room temperature slightly increased when the monoaminic chain extender content increased. The increment in the intermolecu-lar interactions between functional groups of the networks chains, ([0-9]{4})ue to the less hindered nitrogen introduced by the monoamine, appears to be the responsible for the observed behavior. Besides, only small variations on the specific volume were observed on increasing the monoamine content, which points out that for a cured epoxy system, the chemical structure of the curing agent is mainly responsible for chain packing in the networks. On the other hand, intermolecular interactions between chains were considered as the key factor for fixing stiffness and strength. Thus, it was observed that the increase of the intermolecular interactions with the monoamine content produced a decrease in the sub-Tgsmall-range cooperative motions, which increased the low-deformation mechanical properties at temperatures between b and a relaxations. This conclusion could be applied to previous investigations with epoxy matrices not fully crosslinked (nonstoichiometric or noncompletely cured formulations). Finally, it was found that fracture properties do not significantly depend either on the hole volume or on the intermolecular interactions. Fracture properties are more dependent on the crosslink density and the glass transition temperature. © 2009 Wiley Periodicals, Inc.